Is fetal isolated double renal collecting system an indication for chromosomal microarray?. (4th March 2021) - Singer, Amihood; Maya, Idit; Frumkin, Ayala; Zeligson, Sharon; Josefsberg, Sagi Ben Yehoshua; Berger, Racheli; Shachar, Shay Ben; Sagi-Dain, Lena
Abstract: Introduction: Duplication of the renal collecting system is one of the most common variants of urinary tract anatomy. The objective of our study was to examine the risk for chromosomal aberrations in this isolated prenatal sonographic finding. Methods: Data from all chromosomal microarray analyses (CMA) reported to the Ministry of Health between January 2013 and September 2017 were retrospectively obtained from a computerized database. All pregnancies with a sonographic diagnosis of the isolated duplex renal collecting system and documentation of CMA result were included. Rate of abnormal CMA findings was compared to the general population risk, based on a systematic review encompassing 9272 cases with normal ultrasound and a local data of 5541 pregnancies undergoing CMA due to maternal request. Results: Two pathogenic CMA finding was found amongst 143 pregnancies with double collecting system (1.4%), not significantly different from the risk for abnormal CMA results in the general population. In addition, five variants of unknown significance were demonstrated (3.5%). Conclusion: To our best knowledge, this analysis is the first report describing the rate of chromosomal anomalies in pregnancies with isolated duplex renal collecting system. Its results suggest that routine invasive prenatal testing with CMA analysis in such cases is no more useful than in the general population. Prospective well-adjusted studies are needed to guide the optimal management of these pregnancies.